Traditional Chinese Medicine: A promising strategy to regulate inflammation, intestinal disorders and impaired immune function due to sepsis - Xu-Hua Wang; Ding-Qiao Xu; Yan-Yan Chen; Shi-Jun Yue; Rui-Jia Fu; Lu Huang; Yu-Ping Tang (Frontiers Media S.A., 2022)
GRAPHICAL ABSTRACT